2010
DOI: 10.1186/1475-2875-9-239
|View full text |Cite
|
Sign up to set email alerts
|

Arm-in-cage testing of natural human-derived mosquito repellents

Abstract: BackgroundIndividual human subjects are differentially attractive to mosquitoes and other biting insects. Previous investigations have demonstrated that this can be attributed partly to enhanced production of natural repellent chemicals by those individuals that attract few mosquitoes in the laboratory. The most important compounds in this respect include three aldehydes, octanal, nonanal and decanal, and two ketones, 6-methyl-5-hepten-2-one and geranylacetone [(E)-6,10-dimethylundeca-5,9-dien-2-one]. In olfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 33 publications
3
79
0
Order By: Relevance
“…Bed bugs are able to detect C 7 -C 10 aldehydes and sulcatone present in human emanates, similar to other blood-feeding insects (Gikonyo et al, 2002;Birkett et al, 2004;Ghaninia et al, 2008;Logan et al, 2008;Logan et al, 2009;Syed and Leal, 2009;Logan et al, 2010). Quantitative differences in the amount of these compounds in headspace volatile extracts collected from a group of volunteers modulate the behavioural response of bed bugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bed bugs are able to detect C 7 -C 10 aldehydes and sulcatone present in human emanates, similar to other blood-feeding insects (Gikonyo et al, 2002;Birkett et al, 2004;Ghaninia et al, 2008;Logan et al, 2008;Logan et al, 2009;Syed and Leal, 2009;Logan et al, 2010). Quantitative differences in the amount of these compounds in headspace volatile extracts collected from a group of volunteers modulate the behavioural response of bed bugs.…”
Section: Discussionmentioning
confidence: 99%
“…Aldehydes alone appear to elicit attraction in various blood-feeding insects when presented at relevant doses. For example, tsetse flies, Glossina morsitans, fly upwind in presence of a synthetic blend of six aldehydes (Gikonyo et al, 2003), C. quinquefasciatus is caught in traps baited with nonanal (Syed and Leal, 2009) and the addition of C 8 -C 10 aldehydes significantly increases the number of A. gambiae and C. quinquefasciatus landing on a human arm (Logan et al, 2010). In contrast, sulcatone has been shown to inhibit the final approach and landing of different haematophagous insects such as cattle flies (Birkett et al, 2004), and the mosquitoes A. aegypti, A. gambiae and C. quinquefasciatus (Logan et al, 2008;Logan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additional aldehydes (hexanal, octanal, Z-4-decenal) and hexanoic acid, produced by Aethia cristatella Pallas, the crested auklet, have been reported as repellents for mosquitoes (Douglas et al 2005). Logan et al (2008Logan et al ( , 2010 found octanal, nonanal, and decanal as attraction inhibitors and repellents of Ae. aegypti, with decanal as the most potent repellent of the three aldehydes.…”
Section: Treatmentmentioning
confidence: 97%
“…Expression levels and allelic sensitivity of this receptor to 6-methyl-5-hepten-2-one vary across two subspecies of A. aegypti that differ in their preference for humans and correlate positively with preference for human hosts across populations and hybrids of the two subspecies [33]. However, others studies have reported that 6-methyl-5-hepten-2-one is a potent natural repellent found in skin [34,35], and additional studies are required to understand these confounding results.…”
Section: Introductionmentioning
confidence: 99%
“…Natural repellents have also been identified from a variety of plant sources, and more recently, from volatiles found in the skin of humans found to be minimally attractive to mosquitoes [35,56]. Identical twins are more similarly attractive to mosquitoes than are fraternal twins, suggesting a genetic basis [57].…”
Section: Introductionmentioning
confidence: 99%